Wire arc additive manufacturing of a high strength steel - Guo, Bing (Nanyang Technological University, 2022)
Due to the high deposition rates of wire arc additive manufacturing (WAAM) process, it allows quick manufacture of massive structural components. In this study, WAAM process is utilised to prepare three different samples at 150°C, 350°C and 600°C interpass temperatures, using a high strength low alloy (HSLA) steel metal-cored wire as a feedstock. Cold metal transfer (CMT) will be the main welding process used to produce the sample.